(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In This Paper We discuss about the empowerment of women in panchayati raj The Panchayati Raj system can achieve its purpose only by the honesty and spirit of social service of the people. When the Panchayat are able to do their full duties, the State will certainly become strong and rich Panchayati Raj System generally refers to the rural local self-government system in India. The Panchayati Raj institutions (PRI) consists of a three-tier system at district, zilla, and village level. n 1992, vide 73rd constitutional amendment, part IX titled “The Panchayats” were introduced in the Constitution of India. Panchayat System or rural local self-government means the ruling of a local area by a body of people of the same locality, which is mainly under the control of the State Government.